2016
DOI: 10.1021/acssuschemeng.6b00335
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Appropriate Band-Edge-Staggered Heterosemiconductors with Optically Activated Au Nanoparticles via Click Chemistry for Photoelectrochemical Water Splitting

Abstract: Semiconductor-mediated photoelectrochemical (PEC) water splitting to generate hydrogen and oxygen has gained tremendous attention as it has the capability to overcome the world energy crisis. However, limited solar light absorption and a high charge carrier recombination rate are major bottlenecks in achieving the desired efficiency of PEC devices. Fabrication of semiconductor−metal/metal oxide heterostructure holds a great promise to overcome these bottlenecks as it facilitates solar light absorption, separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
(75 reference statements)
2
21
0
Order By: Relevance
“…The overall polarization resistance ( R p ) which is the sum of R t and R a , is in order of Li/D−Li‐>Ox/Red‐>crystalline Co 3 O 4 . Further, we have calculated the polarization resistance per site ( R P / C dl ), which gives the overall resistance per site for the OER reaction . The R P / C dl is least for the Li/D−Li−Co 3 O 4 followed by the Ox/Red‐ and crystalline Co 3 O 4 attributed to the combination of lowering of overpotential and increasing in conductivity and shows a trend of OER activity at the corresponding electrode surface and well matches with specific activity shown in Table .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The overall polarization resistance ( R p ) which is the sum of R t and R a , is in order of Li/D−Li‐>Ox/Red‐>crystalline Co 3 O 4 . Further, we have calculated the polarization resistance per site ( R P / C dl ), which gives the overall resistance per site for the OER reaction . The R P / C dl is least for the Li/D−Li−Co 3 O 4 followed by the Ox/Red‐ and crystalline Co 3 O 4 attributed to the combination of lowering of overpotential and increasing in conductivity and shows a trend of OER activity at the corresponding electrode surface and well matches with specific activity shown in Table .…”
Section: Resultssupporting
confidence: 69%
“…The rate determining parameter for the OER reaction R a , which is the charge-resistance offered by the reaction adsorbates on the surface of the catalyst is least for Li Further, we have calculated the polarization resistance per site (R P / C dl ), which gives the overall resistance per site for the OER reaction. [35] The R P / C dl is least for the Li/DÀ LiÀ Co 3 O 4 followed by the Ox/Red-and crystalline Co 3 O 4 attributed to the combination of lowering of overpotential and increasing in conductivity and shows a trend of OER activity at the corresponding electrode surface and well matches with specific activity shown in Table 1. The stability of crystalline and both types of amorphous and crystalline Co 3 O 4 electro-catalysts are investigated by chronoamperometry in 1.0 M NaOH at 0.6 V vs Ag/AgCl for 10 hrs (Figure 9).…”
Section: Electrochemical Oer Activity Of Treated Co 3 Osupporting
confidence: 70%
“…Lattice‐mismatch leads to the lowering of the stability of hetero‐structure and promotes defect formation at the interface. However, the probability of formation of interfacial defects can be lowered by either (a) formation of heterostructures with different polymorphs of the same material as the variation in crystal structure might be gradual (F. Cao et al, 2016; Pala, 2020; Rashmi & Pala, 2019; Saha et al, 2017; P. Sun et al, 2013; Zhao, Zhu, Li, & Liu, 2015) or (b) through “click” chemistry between azide and alkyne functionalized particles wherein the intermediate five‐membered cyclic structure act as a conducting bridge of charge‐carriers between both of the heterostructure forming material (Behara et al, 2016; Upadhyay et al, 2013, 2016). The synthesis approaches for stabilization of native/non‐native semiconductor junctions have already been addressed in reviews and the interested reader is directed to them for further elaboration (Pala, 2020; Saha et al, 2017).…”
Section: Electrocatalytic and Photo‐electrocatalytic Reaction And Nonmentioning
confidence: 99%
“…However, it has often been observed that the best properties have been found with noble metal or earth‐scarce materials. For example, maximum efficiency in the plasmonic photo‐electrochemical cell (PEC) has been found with Au (Brongersma, Halas, & Nordlander, 2015; Han, Qi, Tang, Gong, & Xu, 2019; J. Lee, Mubeen, Ji, Stucky, & Moskovits, 2012; A. P. Upadhyay et al, 2016). The maximum hydrogen evolution reaction (HER) rate for EC and fuel cell is observed with Pt electrocatalyst (Nørskov et al, 2004; Ojha, Saha, Dagar, & Ganguli, 2018; Xie & Xie, 2015; H. Xu, Ci, Ding, Wang, & Wen, 2019; Zheng, Jiao, Vasileff, & Qiao, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Twos emicircles were observed in EIS as reported before in similar photoelectrodes. [10] Bisquert et al proposed that each semicircle represents ac apacitive resistive (RC) elementd ue to charge-transfer processes in the photoelectrode and between the photoelectrode/electrolyte interface. [10b] Accordingly,t he first semicircle in the high-frequency range was attributed to the impedance given by charget ransfer at the electrode and the second semicircle at low-frequency range has been related to the charge-transfer impedance of electron-recombination reactions at the semiconductor/electrolyte interface.…”
mentioning
confidence: 99%